Effects of HRV-guided vs. predetermined block training on performance, HRV and serum hormones - Nuuttila, O.-P.; Nikander, A.; Polomoshnov, D.; Laukkanen, J. A.; Häkkinen, K. (International Journal of Sports Medicine, 2017)
The aim of this study was to compare heart rate variability -guided (HRVG) and predetermined (PD) block periodization of high intensity aerobic training (HIT). Endurance performance, neuromuscular performance, heart rate variability (HRV) and serum hormone concentrations were measured before, in the middle and after the 8-week training period in 24 endurance trained males. Both groups improved significantly maximal treadmill velocity (Vmax) (p<0.001) and 3000?m running performance (HRVG; p<0.001 and PD; p=0.001). The relative changes in Vmax and countermovement jump were significantly greater in HRVG (p<0.05). Nocturnal heart rate decreased in both groups (p<0.01), but HRV (RMSSD, LF and TP) increased significantly only in HRVG (p<0.05). The significant increase in serum testosterone concentration was observed from mid to post in HRVG (p<0.05). Significant correlations were found between individual Vmax changes and absolute serum testosterone levels. Individual baseline level of HF correlated significantly with Vmax changes in PD. Block periodization of HIT seems to be an effective way to improve endurance and running performance in already endurance trained males. Based on training induced increases in endurance and neuromuscular performance combined with significant changes in HRV and serum testosterone levels observed in HRVG, individually HRV -guided block training may be more optimal compared to predetermined training